View of the Sitaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Chandrabhaga is well-known for its artistic temples, with the Sitaleshwar Temple being the most prominent one. It is an east-facing temple. Despite having been damaged during an invasion, efforts were made to restore and repair the temples. The surviving portion of the Sitaleshwar Temple holds considerable importance, featuring a square garbhagriha (sanctum sanctorum), antarala (vestibule or antechamber), and a mandapa (pillared hall).